Penerapan NodeMCU ESP8266 Smart Fish Pada Pakan Ikan Lele Berbasis Internet of Things Terhadap Budikdamber - Muhammad Tri Handika Pangestu; Susanna Dwi Yulianti Kusuma (CV. Multi Kreasi Media, 2023)
The development of information technology that is developing creates not only to complement, but now it has become a necessity, one of which is in the world of animal husbandry, technology that has developed rapidly provides a wide variety of automatic device options that are created for personal and group convenience because they are assisted in launching professional activities or breeders' hobbies more efficient in managing their livestock. One of them is a fish feed system based on the Internet of Things. Challenges arise when the farm has to be left because the owner is busy and there is no time to feed the fish farm. Therefore, this research was conducted with the aim of overcoming problems with aquaculture managers who cannot provide feed directly to the cultivation site or provide feed at the right time due to having busy things to do. NodeMCU can be used as a device that accepts the input and output of a sensor and as a device to connect to the internet because NodeMCU is equipped with an ESP8266 chip, by adding a servo motor it can connect to the internet, feeding can be done remotely. Users can monitor using telegram bots with available features. With this system, it can overcome if the owner of the cultivation is busy outside and there is no time to provide feed directly, by utilizing the Internet of Things, the cultivation manager can feed remotely without having to visit the place of cultivation directly.